DAMAGES OF Telemus chapadanus (Casey 1922) ON ARATICUM BLOOM (Annona crassiflora Mart.) IN THE GOIÁS STATE - Braga Filho, Juracy Rocha Rocha (2007)
Araticum (Annona crassiflora) is a native fruit species of the Annonaceae family that grows throughout State of Goiás, Brazil. The objective of this study was to evaluate and describe damages by Telemus chapadanus to araticum flowers and the damaging influence on the number of produced fruits. This research was developed from August through December, 2001 on 23 eight years old plants of araticum, belonging to the ";ex situ"; collection of native fruit trees at the ";Escola de Agronomia e Engenharia de Alimentos, Universidade Federal de Goiás";, in Goiânia-GO. During budding period the plants have been weekly monitored for button, flower, and fruit counting and evaluation. The damages were evaluated in three stages. In the first stage, the insects on floral buttons and flowers were weekly quantified. In the second stage, damages were evaluated in eighty damaged floral buttons, removed at random from eighty plants, brought to the laboratory for damage characterization and description. In the third stage, the damages on the number of produced fruits up to the 16th week were evaluated. For this purpose 180 attacked floral buttons from fourteen plants and 87 not attacked from sixteen plants were marked. Results lead to the conclusion that T. chapadanus is an insect that causes damages to the araticum, the more intensive attack occurring at the blooming stage with perforation of petals and reproductive apparatus. However, about 50% of plant floral buttons have been aborted independently of T. chapadanus attack. KEY-WORDS: Insecta; Annonaceae; native fruit plant.